Understanding Viruses - Teri Shors (Jones & Bartlett Learning, 2013)
The Second Edition of Understanding Viruses provides a balanced approach to this fascinating discipline, combining the molecular, clinical, and historical aspects of virology and gives a comprehensive introduction to human viral diseases. Chapters discussing speci? c viral diseases weave in an epidemiological and global perspective and include treatment and prevention information. With a wealth of student and instructor support tools, Understanding Viruses is an accessible, exciting, and engaging text for your virology course.